Life-period associations of body mass index with adult carotid intima-media thickness : The Bogalusa heart study and the cardiovascular risk in young Finns study - Evans, Jack T.; Buscot, Marie-Jeanne; Fraser, Brooklyn J.; Juonala, Markus; Guo, Yajun; Fernandez, Camilo; Kähönen, Mika; Sabin, Matthew A.; Armstrong, Matthew K.; Viikari, Jorma S.A.; Bazzano, Lydia A.; Raitakari, Olli T.; et al. (Elsevier, 2025)
Objective
Child and adult body mass index (BMI) associates with adult carotid artery intima-media thickness (cIMT). However, the relative contribution of BMI at different life-periods on adult cIMT has not been quantified. This study aimed to determine the life-course model that best explains the relative contribution of BMI at different life-periods (childhood, adolescence, and young-adulthood) on cIMT in adulthood.
Methods
BMI was calculated from direct measurements of height and weight at up to seven time-points from childhood to adulthood (1973–2007) among 2485 participants of the Cardiovascular Risk in Young Finns Study (YFS) and 1271 participants in the Bogalusa Heart Study (BHS). BMI measures at three ages representative of childhood (9-years), adolescence (18 years) and young-adulthood (30 years) life-periods were used. B-mode ultrasound was used to measure common cIMT in adulthood (>30 years). Associations were evaluated using the Bayesian relative life-course exposure model.
Results
In both cohorts, cumulative exposure to higher levels of BMI across the life-course was associated with greater cIMT. Of the examined life-periods, BMI in young-adulthood provided the greatest relative contribution towards the development of adult cIMT for YFS (49.9 %, 95 % CrI = 34–68 %) and white BHS participants (48.6 %, 95 % CrI = 9–86 %), whereas BMI in childhood had the greatest relative contribution for black BHS participants (54.0 %, 95 % CrI = 8–89 %).
Conclusion
Although our data suggest sensitive periods in the life-course where prevention and intervention aimed at reducing BMI might provide most benefit in limiting the effects of BMI on cIMT, maintaining lower BMI across the life-course appears to be optimal.